VERBAL AND VISUAL SIGNS FOUND IN Y.O.U COSMETIC ADVERTISEMENTS - Putu Ayu Vinka Maharani; I Wayan Juniartha (JURIHUM : Jurnal Inovasi dan Humaniora, 2024)
The aim of this study is to find out verbal and non-verbal sign in Y.O.U Cosmetic advertisements. While these Y.O.U Cosmetics Advertisements aim to sell us products, they also communicate powerful messages through the clever use of semiotics, the study of signs and symbols. Verbal and non-verbal signs, especially in advertisements, are very important, which function as intermediaries for the intent and purpose of the advertisement. The method that was applied in this research is descriptive qualitative method. The result of this shows 30 denotative meanings and 21 connotative meanings for verbal and nonverbal signs